2016
DOI: 10.12968/bjon.2016.25.13.757
|View full text |Cite
|
Sign up to set email alerts
|

A study into psychosocial factors as predictors of work-related fatigue

Abstract: Psychosocial factors were good predictors of work-related fatigue. A range of psychosocial factors were established, however more research is required to determine all possible causation factors of nurses' work-related fatigue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
36
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 18 publications
6
36
3
Order By: Relevance
“…The results align with the findings of a study by Khadan et al (2017) showing that COF increases after work duration of 6 years and above. On the other hand, our findings revealed that the mean of COF in nurses aged 30-39 years is 3 points higher than those who are less than 30 years old; this contrasted the findings of Winwood, Winefield, and Lushington (2006) (Rahman et al, 2016). A study by Barker and Nussbaum (2011) that assessed perceived mental and physical dimensions of fatigue levels among nurses showed that mental fatigue levels (lack of motivation) are higher than physical fatigue levels (physical exertion).…”
Section: Chronic Occupational Fatiguecontrasting
confidence: 96%
See 2 more Smart Citations
“…The results align with the findings of a study by Khadan et al (2017) showing that COF increases after work duration of 6 years and above. On the other hand, our findings revealed that the mean of COF in nurses aged 30-39 years is 3 points higher than those who are less than 30 years old; this contrasted the findings of Winwood, Winefield, and Lushington (2006) (Rahman et al, 2016). A study by Barker and Nussbaum (2011) that assessed perceived mental and physical dimensions of fatigue levels among nurses showed that mental fatigue levels (lack of motivation) are higher than physical fatigue levels (physical exertion).…”
Section: Chronic Occupational Fatiguecontrasting
confidence: 96%
“…This study shows that COF exists among Lebanese nurses working in acute care settings. The reported mean COF level was 78, which is relatively high compared with other studies that reported means of 50 (Barker & Nussbaum, 2011) and 41 (Rahman, Abdul-Mumin, & Naing, 2016). Looking at the relationship with individual factors, our results showed that the mean of COF among nurses with 5-10 years of experience is 3.89 points higher than those with less than 5 years of experience.…”
Section: Chronic Occupational Fatiguecontrasting
confidence: 59%
See 1 more Smart Citation
“…A previous study found that as high as 80% of nurses reported insufficient time for rest (Sharma et al., ). Another study reported that approximately 36% of the variance of chronic fatigue was related to stress (Rahman, Abdul‐Mummin, & Naing, ). These studies also indicated that work‐related pressure and other factors influence the retention levels and turnover rates of professional nurses internationally.…”
Section: Introductionmentioning
confidence: 99%
“…The association between psychosocial risk factors and occupational stress is a topic studied in different populations around the world, reporting that the increase of the frequency and intensity of these risk factors, is usually accompanied by an increase in the occupational stress levels, as well as in the negative consequences for the health (Tuvesson & Eklund, 2014;Gerr et al, 2014;Rahman, Abdul-Mumin, & Lin, 2016). However, only few researches have approached the psychosocial area with the service station attendants, a group that, as mentioned before, performs under conditions that can be identify as important psychosocial risk factors, besides the chemical and physical factors broadly studied before.…”
Section: Introductionmentioning
confidence: 99%